Reconstructed evolutionary history of the yeast septins Cdc11 and Shs1. Issue 1 (7th December 2020) - Takagi, Julie; Cho, Christina; Duvalyan, Angela; Yan, Yao; Halloran, Megan; Hanson-Smith, Victor; Thorner, Jeremy; Finnigan, Gregory C
Abstract: Septins are GTP-binding proteins conserved across metazoans. They can polymerize into extended filaments and, hence, are considered a component of the cytoskeleton. The number of individual septins varies across the tree of life—yeast ( Saccharomyces cerevisiae ) has seven distinct subunits, a nematode ( Caenorhabditis elegans ) has two, and humans have 13. However, the overall geometric unit (an apolar hetero-octameric protomer and filaments assembled there from) has been conserved. To understand septin evolutionary variation, we focused on a related pair of yeast subunits (Cdc11 and Shs1) that appear to have arisen from gene duplication within the fungal clade. Either Cdc11 or Shs1 occupies the terminal position within a hetero-octamer, yet Cdc11 is essential for septin function and cell viability, whereas Shs1 is not. To discern the molecular basis of this divergence, we utilized ancestral gene reconstruction to predict, synthesize, and experimentally examine the most recent common ancestor ("Anc.11-S") of Cdc11 and Shs1. Anc.11-S was able to occupy the terminal position within an octamer, just like the modern subunits. Although Anc.11-S supplied many of the known functions of Cdc11, it was unable to replace the distinct function(s) of Shs1. To further evaluate the history of Shs1, additional intermediates along a proposed trajectory from Anc.11-S to yeast Shs1 were generated and tested. We demonstrate that multiple events contributed to the current properties of Shs1: (1) loss of Shs1–Shs1 self-association early after duplication, (2) co-evolution of heterotypic Cdc11–Shs1 interaction between neighboring hetero-octamers, and (3) eventual repurposing and acquisition of novel function(s) for its C-terminal extension domain. Thus, a pair of duplicated proteins, despite constraints imposed by assembly into a highly conserved multi-subunit structure, could evolve new functionality via a complex evolutionary pathway.